Correlation of Aging and Segmental Choroidal Thickness Measurement using Swept Source Optical Coherence Tomography in Healthy Eyes. - Yu Wakatsuki; Ari Shinojima; Akiyuki Kawamura; Mitsuko Yuzawa (PLoS ONE, 2015)
To assess and compare choroidal thickness changes related to aging, we determined whether changes are due to thinning of the choriocapillaris plus Sattler's (CS) layer and/or the large vessel layer in healthy eyes using swept-source optical coherence tomography (SS-OCT) at a wavelength of 1,050-nm.We studied 115 normal eyes of 115 healthy volunteers, all with refractive errors of less than -6 diopters. All 115 eyes underwent analysis of choroidal thickness at the fovea, the CS layer and the large choroidal vessel layer. In 68 of the 115 eyes, choroidal thickness was determined at five sites (the fovea, and superior, inferior, nasal, and temporal sites) using SS-OCT with an Early Treatment of Diabetic Retinopathy grid scan.Total choroidal thicknesses at each of the five sites were related to subject age (P<0.0001). The choroid was thinnest at the nasal site, followed by the temporal, inferior, superior and finally the subfoveal site itself. The total choroidal thickness at the nasal site was significantly less than those at the other four sites (p<0.05). The CS layer showed thinning which correlated with age (P<0.0001). The thickness of the choroidal large vessel layer also decreased with age (p = 0.02). Subfoveal choroidal thickness was calculated as follows: 443.89-2.98×age (μm) (P<0.0001).Subfoveal choroidal thickness decreases by 2.98 μm each year. Total choroidal thickness diminishes with age. The CS and large vessel layers of the choroid at the subfovea showed significant decreases, though only the former correlated strongly with age.